2019
DOI: 10.1016/j.jarmac.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Two eyewitnesses are more persuasive than one except when they remember a suspect's feature.

Abstract: Are jurors more likely to convict a suspect who has been identified by multiple eyewitnesses than by a single one? Participants saw a lineup of faces with one face highlighted as having been identified by either one or two highly confident eyewitnesses. Participants estimated the likely guilt of the suspect. Two eyewitnesses were not more persuasive than one when either the single or the multiple eyewitnesses had provided a featural justification about their identification (e.g., "I remember his eyes"). But, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
(46 reference statements)
1
8
0
Order By: Relevance
“…In Experiments 1 and 2, participants rated the identical confidence statements about a lineup identification as meaning a lower level of certainty when they referenced a facial feature (e.g., “I am very confident. I remember his eyes”), as compared to when the statement was presented alone (e.g., “I am very confident”), replicating past research on the featural justification effect (e.g., Dobolyi & Dodson, 2018; Dodson & Dobolyi, 2015; Slane & Dodson, 2019). Participants’ perceptions of the witness’s certainty were affected by their impressions of the witness’s accuracy (Cash & Lane, 2017; Dodson & Dobolyi, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…In Experiments 1 and 2, participants rated the identical confidence statements about a lineup identification as meaning a lower level of certainty when they referenced a facial feature (e.g., “I am very confident. I remember his eyes”), as compared to when the statement was presented alone (e.g., “I am very confident”), replicating past research on the featural justification effect (e.g., Dobolyi & Dodson, 2018; Dodson & Dobolyi, 2015; Slane & Dodson, 2019). Participants’ perceptions of the witness’s certainty were affected by their impressions of the witness’s accuracy (Cash & Lane, 2017; Dodson & Dobolyi, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Criminal cases involving eyewitness testimony commonly include multiple eyewitnesses (e.g., Tollestrup et al, 1994; Wright & McDaid, 1996; Yuille & Tollestrup, 1992), yet few studies have examined the influence of single versus multiple eyewitnesses on juror decision making. One study told mock jurors that either one or two highly confident eyewitnesses had identified a suspect (Slane & Dodson, 2019). Each eyewitness provided a confidence statement with a featural justification, a general recognition justification, or no justification.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon occurs when perceptions of eyewitness confidence and accuracy decrease when a witness references a nondistinctive, physical feature of the suspect as a justification for their identification (e.g., “I am certain. I would never forget his nose” see Cash & Lane, 2017, 2021; Dodson & Dobolyi, 2015, 2017; Grabman & Dodson, 2019; Slane & Dodson, 2019). Despite this being an eyewitness scenario, the overarching theme is that additional information perceived as “unwarranted” detracts from the credibility of something that is being assessed.…”
Section: Discussionmentioning
confidence: 99%